(untitled) (EAAE Annual Conference Proceedings, 2023)
Design Build Studios (DBS) are special pedagogical tools in architectural education. They offer 1:1 scale construction experience, a chance to utilize the creativity of the students for the public benefit, are based on collaboration and teamwork. In the curriculum of MEF University Architecture program there is a DBS component that is compulsory for all students.